Homoseksualitas: Tinjauan Kesehatan Reproduksi - Wahyuni, Budhy (Sunan Kalijaga State Islamic University & The Asia Foundation, 2003)
The issue of homosexuality brings about various viewpoints that are controversial from any aspect. In terms of health, for example, many people link homosexuality as being the cause of the spread of HIV/AIDS, even though homosexuals themselves do not accept this accusation. In this article, Budi Wahyuni endeavours to look more